Comparative Study of References and Protein Quantifications Using Biuret-Spectrophotometric Method - Ahmad Syauqi; Muhamad Fuadi; Hari Santoso (Chimica et Natura Acta, 2018)
Comparison between the references and the quantification of biuret standard curves can be performed using statistical methods. The objective of this study was to select a method of protein quantification of the biuret-spectrophotometric based on the similar standard curve of the compound. The study used experimental methods in the laboratory and references from a comparative scheme of mean that has categories of statistics called academic and practical terms. Two standard curves were tested with the reference data. The academic way was performed with a comparison of 11.779-12.401% confidence, and the quantification of the results of the protein mean of 8.211% and 10.17% showed no significant difference. The practical methods were carried out with the original reference data of 10.8-12.8%, and the result of the test confidence values of 9.163-11.180% and 7.596-8.826% showed different accuracy results. The quantifications of the protein biuret method displayed different results on how to compare according to academic and practical ways. The quantification method using the Biuret-spectrophotometric practical way shows accuracy by a certain standard curve compared with the original values of references.